The Impact of Malaria among pregnant women in Papua New Guinea: A Systematic Review of Epidemiology, Prevention & Treatment. - Susina Yatapya; Dwi Sarwani Sri Rejeki; Siwi Pramatama Mars Wijayanti (Insights in Public Health Journal, 2023)
BACKGROUND: Malaria in pregnancy is a serious public health problem in Papua New Guinea (PNG), where both Plasmodium falciparum and P. vivax are endemic. Malaria infection during pregnancy can cause maternal anemia, low birth weight, preterm delivery and congenital malaria, which can have serious consequences for the health and survival of mothers and infants. The aim of this literature review was to assess & summarize the current state of knowledge and practice on malaria epidemiology, prevention and treatment in pregnant women and their newborns in PNG, based on ten research papers published from 1986 to 2021. Subjects and Methods: This was a systematic review conducted by searching articles from Google Scholar database and Mendeley Elsevier database and PubMed. The inclusion criteria were namely articles published in 1900 to 2022 years, cross sectional design study, and using quantitative method. The study subjects were pregnant women who visited antenatal clinics with or without malaria, research locations in Papua New Guinea. The exclusion criteria were articles that did not available in full text and located not in Papua New Guinea. The articles were then critically appraised and synthesized according to five main themes: anemia and iron deficiency, submicroscopic malaria infections, placental malaria infection, and knowledge, attitudes and practices concerning malaria in pregnancy & congenital malaria. Results: A total of 10 papers were included in the review, covering various aspects of malaria epidemiology, prevention and treatment in pregnant women and their newborns in PNG. The main findings of the papers were: (1) anemia was very common and associated with splenomegaly, iron deficiency and malaria infection; (2) submicroscopic infections were common, but not associated with maternal anemia or low birth weight; (3) placental malaria infection was detected in 18.5% of placentas, and was associated with maternal anemia, low birth weight and preterm delivery; (4) there was a general awareness of the term â€œmalariaâ€, but it was often confused with other illnesses or pregnancy symptoms; (5) congenital malaria infection was detected in 5.6% of newborns, mostly due to P. falciparum. Conclusion: This literature review provided useful evidence and recommendations for improving malaria prevention and control in pregnant women and their newborns in PNG, but also highlighted the need for more research and action to address the remaining challenges and gaps. The review concluded that malaria in pregnancy is a serious public health problem in PNG that requires comprehensive and integrated approaches to achieve its elimination by 2030. Keywords: Malaria in pregnancy, Papua New Guinea, Anemia, Submicroscopic malaria infections, Placental malaria infection